2009
DOI: 10.1074/jbc.m109.003277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pin1 or Microtubule Binding on Dephosphorylation of FTDP-17 Mutant Tau

Abstract: Neurodegenerative tauopathies, including Alzheimer disease, are characterized by abnormal hyperphosphorylation of the microtubule-associated protein Tau. One group of tauopathies, known as frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17), is directly associated with mutations of the gene tau. However, it is unknown why mutant Tau is highly phosphorylated in the patient brain. In contrast to in vivo high phosphorylation, FTDP-17 Tau is phosphorylated less than wild-type Tau in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…Tau-We have reported previously that recombinant Tau phosphorylated by Cdk5-p35 is dephosphorylated by PP2A faster in WT mouse brain extract than in Pin1-deficient mouse brain extract (39). This result suggests that Pin1 recognizes Cdk5-phosphorylated Tau to stimulate its dephosphorylation.…”
Section: Cdk5 Phosphorylation Is a Prerequisite For Pin1 Binding Tomentioning
confidence: 85%
See 2 more Smart Citations
“…Tau-We have reported previously that recombinant Tau phosphorylated by Cdk5-p35 is dephosphorylated by PP2A faster in WT mouse brain extract than in Pin1-deficient mouse brain extract (39). This result suggests that Pin1 recognizes Cdk5-phosphorylated Tau to stimulate its dephosphorylation.…”
Section: Cdk5 Phosphorylation Is a Prerequisite For Pin1 Binding Tomentioning
confidence: 85%
“…These Pin1 mutants did not bind to phosphorylated Tau (Fig. 2C) (8,11,29,39,50). Some of these sites may be minor sites that were identified with phosphorylation-specific antibodies.…”
Section: Pin1 Binds To Tau When Phosphorylated By Cdk5-p25 and Gsk3␤ mentioning
confidence: 97%
See 1 more Smart Citation
“…␤-Adducin is the third substrate of Cdk5 demonstrated to display relative resistance to phosphatases (others being CRMP2 and Tau (42,43)), but this is the first time a GSK3 phosphosite has been demonstrated to display relative resistance. We previously showed that resistance to phosphatases was in part due to the presence of a basic residue at the ϩ3 position, which stabilizes the negative charge on the phosphorylated serine (42).…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that other kinases might also target these sites or that other kinases can compensate for the loss of Cdk5 and GSK3 activity. Alternatively, removal of phosphate from these sites by phosphatases might be very inefficient, as has previously been shown for phosphosites in CRMP2 and Tau that are relatively resistant to dephosphorylation by phosphatases (42,43). To determine whether any phosphosites in ␤-adducin display similar resistance to phosphatases, a rat brain lysate was incubated without phosphatase inhibitors at 30°C for up to 4 h. Relative rates of dephosphorylation at each site by endogenous phosphatases were measured using Western blotting.…”
Section: ␤-Adducin Phosphosites Display Relative Resistance To Phosphmentioning
confidence: 99%